Perception of brittle nails in dermatologic patients: a cross-sectional study - Giulio Cesar Gequelim; Cynthia Yone Kubota; Sarah Sanches; Daniela Dranka; Marcelo Murilo Mejia; Fernando Mitsuo Sumiya; Juliano Vilaverde Schmitt (Sociedade Brasileira de Dermatologia, 2013)
Brittle Nails Syndrome is characterized by fragility of the nail plate, affecting 27% of women. We evaluated dermatology patients in a cross-sectional study about perception of nail fragility. One hundred and thirtyeight women were included, with median age of 36.5 years. Nail examination showed changes in 57% and 49% reported nail fragility. The first three fingernails were the most affected. Onychoschizia was related to onychophagia (OR = 3.29), housework (OR = 2.95) and water contact (OR = 2.44). Onychorrhexis had the strongest association with nail fragility perception (OR = 17.89). The fragility was more perceived by those who were black, of mixed race and atopic, and was associated with depressed mood.